The Effectiveness of the Team Games Tournament (TGT) Learning Model in Enhancing Student Learning Interest in Science Subjects at Madrasah Ibtidaiyah: A Management Perspective - Ikromudin, M. Hasan; Khurin’in Ratnasari (Journal of Educational Management Research, 2025)
The education system plays a vital role in society, especially in the transition from Education 4.0 to 5.0, where technology is increasingly integrated into learning. However, many educators still rely on monotonous methods that fail to engage students. This study aims to improve fourth-grade students' interest in IPAS by implementing the Team Games Tournament (TGT) interactive learning model in the 2024/2025 academic year. Based on classroom observations, the conventional approach was found to be less conducive to active learning. Using a quantitative method with random sampling, the research evaluates the impact of TGT on learning interest and outcomes. The results indicate that TGT can enhance student engagement and academic achievement. Educationally, the study supports the shift toward more interactive and student-centered models. From a management perspective, it underscores the need for innovation in instructional strategies and adaptive leadership in implementing engaging pedagogical methods. These findings underscore the importance of strategic planning and effective resource management in enhancing teaching quality and institutional performance.